2024
DOI: 10.1136/bmjopen-2023-078849
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of attention-deficit hyperactivity disorder in children, adolescents and adults in the Middle East and North Africa region: a systematic review and meta-analysis

Mohammad Al-Wardat,
Mohammad Etoom,
Khader A Almhdawi
et al.

Abstract: ObjectivesTo systematically estimate the overall prevalence of attention-deficit hyperactivity disorder (ADHD) in children, adolescents and adults across the Middle East and North Africa (MENA) region.DesignSystematic review and meta-analysis conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement.Data sourcesMedline and Scopus databases were comprehensively and systematically searched between 1990 and February 2023.Eligibility criteria for selecting stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
1
1
0
Order By: Relevance
“…Overall, participants showed high levels of mental health symptoms, which is consistent with emerging data of student cohorts across disciplines and departments [40]. The prevalence rates of anxiety, depression, and stress in our study align with the average prevalence rate from a previous report that showed that college students have a moderate level of depression and stress and a severe level of anxiety [40][41][42]. In the current study, anxiety was significantly correlated with the expressive suppression ER strategy.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, participants showed high levels of mental health symptoms, which is consistent with emerging data of student cohorts across disciplines and departments [40]. The prevalence rates of anxiety, depression, and stress in our study align with the average prevalence rate from a previous report that showed that college students have a moderate level of depression and stress and a severe level of anxiety [40][41][42]. In the current study, anxiety was significantly correlated with the expressive suppression ER strategy.…”
Section: Discussionsupporting
confidence: 90%
“…Globally, the prevalence of ADHD among children and adolescents raged from 5.29% to 8.0% [ 8 , 49 51 ]. Moreover, according to the systematic review and meta-analysis conducted in the different parts of the continents, the prevalence of ADHD among children and adolescents was found to be 2.9% in Europe [ 52 ], 10.90% in America [ 44 ], 5.9% in Arab Gulf [ 53 ], 10.3% in the Middle East and North Africa [ 54 ] and 5.4% to 8.7% in Africa [ 55 , 56 ]. This shows that a large number of children and adolescents remain affected by ADHD and are facing difficulties associated with the disorder.…”
Section: Introductionsmentioning
confidence: 99%